Peningkatan Hasil Belajar Mahasiswa Melalui Model Pembelajaran Tutor Sebaya - Mahsup Mahsup; Ibrahim Ibrahim; Sintayana Muhardini; Nurjannah Nurjannah; Eka Fitriani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This research aims to describe the learning by applying peer tutor learning model as an effort to improve the learning outcomes in the linear program of fourth semester students in Mathematics education study program of FKIP UM Mataram. The research method used a class action research. The research population was fourth semester students of Mathematics education study program of FKIP UM Mataram, with as many as four students taken as samples. The instruments of the study were the observation results of the learning implementation and the final test result of students study. Analysis of research data on students test results was obtained from the final test result of the learning cycle. The test was said to succeed if 85% of the total students got a value of ≥ 65. Based on the results of the study, the application of peer tutor learning models could improve learning outcomes with the observation result of lecturers and student learning activities were in good criteria. And, the final test score of cycle I had achieved a classical learning standard with a percentage achievement reached 75%.